Overview of Marriage Preparation Among Students in Tasikmalaya - Anissa Salsabilla; Anandha Putri Rahimsyah; Muhammad Muhajirin (Journal of Mental Health and Well-Being in Counseling, 2025)
Marriage is an important developmental stage in early adulthood that requires emotional, psychological, social, and financial readiness. Empirical evidence shows that many students want to get married at a young age without adequate preparation, which can potentially lead to conflict and disharmony. This study aims to determine the readiness of students in Tasikmalaya City to marry based on the early adulthood age group (18–25 years) and gender, as well as to formulate implications for premarital guidance and counseling in higher education. This descriptive quantitative study involved 511 students selected through simple random sampling. The instrument used was the PREPARE Inventory (Fowers & Olson, 1992), adapted by Darajatun (2024), consisting of 11 psychosocial dimensions with a 5-point Likert scale. Data analysis used descriptive statistics in the form of frequency, percentage, mean, and standard deviation. The results showed that 49.5% of students were in the high to very high marriage readiness category, while 50.5% were in the low to very low category. The aspects with the lowest scores included financial management, sexual relationships, and religious orientation. These findings emphasize the need for structured classical counseling services to strengthen students' emotional readiness, relational skills, and financial and spiritual readiness as preparation for entering married life.